Treatment of calcium channel blocker-induced gingival overgrowth without modifying medication. Issue 1 (11th January 2021) - Morikawa, Satoru; Nasu, Mana; Miyashita, Yoko; Nakagawa, Taneaki
Abstract : Gingival overgrowth is a common side effect of calcium channel blockers used in the treatment of cardiovascular diseases. While controversial, management includes discontinuing the calcium channel blocker. We report the case of a 66-year-old Japanese man with hypertension and type 2 diabetes mellitus who was diagnosed with severe periodontitis covering almost all the teeth. The patient had been on nifedipine (40 mg/day) and amlodipine (10 mg/day) medication for 5 years. With his physician's consent, nifedipine was discontinued during his treatment for periodontitis, which consisted of oral hygiene instructions and scaling and root planing on all areas. Gingivectomy was performed on the areas of hard fibrous swelling. Nifedipine was resumed during periodontal treatment when the patient's hypertension worsened. His periodontal scores improved when he resumed treatment. We report that significant improvement in gingival overgrowth can occur with basic periodontal treatment, surgery and sustained intensive follow-up without adjusting calcium channel blockers.